2018
DOI: 10.1371/journal.pone.0204952
|View full text |Cite
|
Sign up to set email alerts
|

GWAS analysis in spring barley (Hordeum vulgare L.) for morphological traits exposed to drought

Abstract: Association analysis based on linkage disequilibrium has become a common and powerful approach for detection of QTLs underlying complex agronomic traits including drought tolerance. To determine marker/trait association, 148 modern European spring barley cultivars were evaluated under drought stress. Associations of morphological traits with AFLP/SSR markers were investigated based on the mixed linear model using the TASSEL3.0. Population structure was estimated using various methods including Bayesian cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 75 publications
3
36
0
Order By: Relevance
“…Thus, it can be proved that MSL and AL have the same controller genomic regions. In non stress conditions, one SSR marker (Bmag0223-170) on chromosome 5H showed significant association with MSL, which was previously reported for plant height (Jabbari et al, 2018). Wang et al (2014) identified four QTLs on chromosomes 1H, 2H, 5H and 7H for spike length.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Thus, it can be proved that MSL and AL have the same controller genomic regions. In non stress conditions, one SSR marker (Bmag0223-170) on chromosome 5H showed significant association with MSL, which was previously reported for plant height (Jabbari et al, 2018). Wang et al (2014) identified four QTLs on chromosomes 1H, 2H, 5H and 7H for spike length.…”
Section: Discussionsupporting
confidence: 68%
“…For awn length, six markers on chromosomes 1H, 3H, 4H and 5H under non stress conditions and four markers on chromosomes 3H, 4H and 5H under Mn stress conditions were identified. Some of these significant markers have been previously reported for internode length, flag leaf width and flag leaf sheath length (Jabbari et al, 2018). Liller et al (2017) detected twelve significant QTLs for awn length located on all chromosomes.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The heritability values observed in this study indicated that the variation in tolerance index (germination in salt divided by germination in DI water) was mainly a factor of salinity concentration with a small genetic component. However, salinity tolerance is an important trait in barley that is inherited quantitatively and strongly influenced by environmental conditions (Jabbari et al, 2018), as indicated by the significant interactions among genotypes, salinity tolerance, and location in this study (Table 1). Estimated heritability defines how a trait is affected by genotype; however, it is not a total quantifier of how genes and the environment govern a phenotype, but specific to the population and environment under study.…”
Section: Barley Reference Genome and High-density Markers Facilitate mentioning
confidence: 70%